Performing Arts Management System of Sanggar V Tunang in Padang City in Organizational Governance and Marketing - Hafizatul Ismi; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to explain and describe the Management System of Performing Arts Sanggar V Tunang in Padang City in Organizational Governance and Marketing. This type of research is qualitative research using describing techniques. The researcher is the primary instrument in this study, with the aid of stationery and cameras as supporting tools. Primary data and secondary data are the two types of data used. This study used a variety of methods to collect data, including observations, interviews, documentation, and literature reviews. using data analysis methods, data presentation and drawing conclusions/verification. This result shows that Sanggar V Tunang has a single leadership management system, in its implementation leaders who have been selected and determined have responsibilities when there is an event or not. The management system rests on organizational governance management and marketing management. Sanggar V Tunang uses its organizational governance by selecting 7 leaders (core dancers) who have covered all jobs and each leader has their own responsibilities in a predetermined position. Marketing activities carried out by studio V Tunang are by promoting through social media such as Instagram, Facebook, and TikTok. Sanggar V Tunang also collaborates with several aisles in Padang City. The target of pamasaran at Sanggar V Tunang is wedding events, government events, community events and others.